Salt-responsive lytic polysaccharide monooxygenases from the mangrove fungus Pestalotiopsis sp. NCi6. Issue 1 (December 2016) - Patel, Ilabahen; Kracher, Daniel; Ma, Su; Garajova, Sona; Haon, Mireille; Faulds, Craig; Berrin, Jean-Guy; Ludwig, Roland; Record, Eric
Abstract Background Lytic polysaccharide monooxygenases (LPMOs) belong to the "auxiliary activities (AA)" enzyme class of the CAZy database. They are known to strongly improve the saccharification process and boost soluble sugar yields from lignocellulosic biomass, which is a key step in the efficient production of sustainable economic biofuels. To date, most LPMOs have been characterized from terrestrial fungi, but novel fungal LPMOs isolated from more extreme environments such as an estuary mangrove ecosystem could offer enzymes with unique properties in terms of salt tolerance and higher stability under harsh condition. Results Two LPMOs secreted by the mangrove-associated fungusPestalotiopsis sp. NCi6 (Ps LPMOA andPs LPMOB) were expressed in the yeastPichia pastoris and produced in a bioreactor with >85 mg L−1 forPs LPMOA and >260 mg L−1 forPs LPMOB. Structure-guided homology modeling of thePs LPMOs showed a high abundance of negative surface charges, enabling enhanced protein stability and activity in the presence of sea salt. BothPs LPMOs were activated by a cellobiose dehydrogenase (CDH) fromNeurospora crassa, with an apparent optimum of interaction at pH 5.5. Investigation into their regioselective mode of action revealed thatPs LPMOA released C1- and C4-oxidized cello-oligosaccharide products, whilePs LPMOB released only C4-oxidized products.Ps LPMOA was found to cleave polymeric cellulose in the presence of up to 6 % sea salt, which emphasizes the use of sea water in the industrial saccharification process with improved ecological footprints. Conclusions Two new LPMOs from the mangrove fungusPestalotiopsis sp. NCi6 were found to be fully reactive against cellulose. The combined hydrolytic activities of these salt-responsive LPMOs could therefore facilitate the saccharification process using sea water as a reaction medium for large-scale biorefineries.